ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA KUALITAS INDIKATOR OUTCOME: STUDI EMPIRIS PADA KABUPATEN/KOTA DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Nugroho, Prayudi; Halim, Abdul (JURNAL INFO ARTHA, 2016)
This research aims at examining the effects of quality of mission, process to determining outcome indicator, culture, commitment, and authority to quality of outcome indicator at local government's RENSTRA and LAKIP documents. This research conducted on 5 local governments of Daerah Istimewa Yogyakarta Province. The respondents are the officials of that local governments. The instrument for collecting data is questioner. The obtained from this research are analyzed with multiple regression analysis. This research finding shows that quality of mission, process to determining outcome indicator, culture, and authority have statistically significant effects to quality of outcome indicator, but commitment hasn't statistically significant effects to quality of outcome indicator.